(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف هذا البحث إلى دراسة محددات سعر الصرف الحقيقي في سورية خلال الفترة 1990-2011. تم تطبيق اختبار متجه الانحدار الذاتي ((VARVectorAuto Regressionلدراسة العلاقة طويلة الأجل بين سعر الصرف الحقيقي والعوامل المؤثرة عليه، كما تمّ تطبيق اختبار غرانجر للسببية Granger Causalityلمعرفة اتجاه العلاقة بين هذه المتغيرات. إلى جانب ذلك، تم تطبيق دوال الاستجابةImpulse Response Functions (IRF) وتحليل مكونات التباين Variance Decomposition لمعرفة مدى مساهمة هذه المحددات في تفسير تقلبات سعر صرف الحقيقي لليرة السورية. تناولت الدراسة ثمانية محددات لسعر الصرف الحقيقي وهي: الاستثمار الأجنبي المباشر، معدل النمو الاقتصادي، العرض النقدي، الإنفاق الحكومي، الانفتاح التجاري، سعر الفائدة الحقيقي، شروط التبادل التجاري، والاستقرار السياسي. توصلت الدراسة إلى أن كل من الاستثمار الأجنبي المباشر، معدل النمو، والانفتاح التجاري يعتبر محددات سعر الصرف الحقيقي في سورية خلال الفترة المدروسة. وقد كان للاستثمار الأجنبي المباشر ومعدل النمو الاقتصادي الأثر الأكبر على سعر الصرف الحقيقي لليرة السورية، في حين كان الانفتاح التجاري هو المحدد الأقل تأثيراً على سعر الصرف الحقيقي في سورية خلال الفترة المدروسة. أمّا بالنسبة لبقية المحددات فلم يكن لها أثر معنوي على سعر صرف الليرة السورية خلال الفترة المدروسة. The purpose of this research is to study the determinants of the real exchange rate in Syria during the period 1990 to 2011. We employed Vector Auto Regression (VAR) model to study the long-term relationship between the real exchange rate and the factors affecting it. Also we applied the Granger causality test to investigate the direction of the relationship between these variables. In addition, the Impulse Response Functions (IRF) and the Variance Decomposition to determine thecontribution of thesedeterminantsin the interpretation ofthe variance oftherealexchangerateof the Syrian pound. Eight possible determinants have been included in the empirical model: Foreign direct investment,realGDPgrowthrate,money supply, government consumption, trade openness,real interest rate, terms of trade, political stability indictor. The variables that have been found to have a long run relationship with the real exchange rate are: theforeign direct investment, real GDP growth rate and trade openness.EspeciallyForeign direct investment and Real GDP growth rate which have the greatest effect on the real exchange rate, while the trade openness had the least effect on the real exchange rate in Syria.Leavingthe other determinants with insignificant effect on real exchange rate in Syria